Successful treatment of pyrotinib for bone marrow metastasis induced pancytopenia in a patient with non‐small‐cell lung cancer and ERBB2 mutation - Yanyan Wu; Jun Ni; Xiaoyan Chang; Xiaotong Zhang; Li Zhang (Thoracic Cancer, 2020)
Abstract ERBB2 mutations are found in about 2% of patients with non‐small cell lung cancer (NSCLC). A recent study reported that pyrotinib (an irreversible pan ErbB inhibitor) had superior antitumor effect compared to other tyrosine kinase inhibitor therapies in patients with ERBB2 mutations. Bone marrow metastasis is rare in lung adenocarcinoma, and has been reported to be associated with poor prognosis. Here, we report the case of a 62‐year‐old female diagnosed with lung adenocarcinoma and bone marrow metastasis. ERBB2 exon 20 insertion mutation was confirmed by next‐generation sequencing (NGS) of lung tissue as well as bone marrow. The patient achieved stable disease and recovery of pancytopenia after two months of pyrotinib therapy. This is the first report of homogenous mutations of ERBB2 detected in bone marrow, as well as a good response of bone marrow to pyrotinib therapy. Key points This is the first report of a homogenous mutation of ERBB2 detected in the bone marrow of an NSCLC patient with bone marrow metastasis. Our patient with NSCLC ERBB2 mutation and bone marrow metastasis responded well to pyrotinib therapy.